Emotional Intelligence Buffers the Effects of Negative Emotions on Job Burnout in Nursing - Szczygiel, Dorota Daniela; Mikolajczak, Moïra (Frontiers in Psychology, 2018)
The study was designed to examine whether trait emotional intelligence would moderate the impact of negative emotions at work on job burnout. A total of 188 female nurses participated in this study and completed measures of trait affectivity, emotional intelligence, anger and sadness at work [over five consecutive days, nurses rated the extent to which they experienced anger-related emotions (i.e., irritation, embitterment and anger) and sadness-related emotions (i.e., depression, disappointment and sadness)], and burnout. The results revealed significant and positive relationships between both types of negative emotions and burnout above and beyond demographics and the nurses’ trait affectivity. Importantly, the study demonstrated that trait emotional intelligence buffers the effects of negative emotions on burnout. Specifically, anger- and sadness-related emotions predicted greater burnout among nurses with low trait emotional intelligence but not among nurses with high trait emotional intelligence. These results suggest that emotional intelligence training could be implemented to prevent the adverse effect of negative emotions felt at work on job burnout.